Development of mathematical model and optimization of GMA welding parameters of IS 2062 grade A steel weldments - Saadat Ali Rizvi; Wajahat Ali (Fracture and Structural Integrity)
In this experimental work, the effects of Gas metal arc (GMA) welding process parameters, such as arc voltage, wire feed speed, and gas flow rate on the mechanical quality of IS 2062 structural steel of grade A have been studied. Process parameters play an important role in determining the weld quality. In this research work the response surface methodology (RSM) via the design expert version 12 (DOE) software was applied to determine the weld quality, for 3D plot, maximize desirability for all response, and also to develop a mathematical model that can predict the main effect of the listed parameters on weld quality i.e. toughness and hardness. A set of experiments has been conducted to collect the response data using a central composite design and ANOVA was used to predict the impact of welding parameters on toughness and hardness. The obtained and predicated results were compared and it was verified that toughness and hardness of weldments are significantly affected by arc voltage and wire feed speed while gas flow rate has a minor effect.